Representasi Perempuan dalam Film Bernuansa Islami - Syiqqil Arofat (Refleksi: Jurnal Kajian Agama dan Filsafat, 2013)
This writing shows that work of film which signs and defines realities through separation and election of meaning network fitting to certain view has limited audiences’ paradigm in defining their social realities; as if what given by film is a usual happening and should be a direction for the audiences to behave and act. The direction then is tightly attached with identification for differing between good and bad, wrong and right, friend and foe, us and them, even the most liked by the audiences is: sexual differentiation between man and woman. In this respect, to be a man or woman is presented as a different experience and cannot be the same in terms of behavior, action and role in whole life aspects. By this meaning construction, cultural hegemony starts.DOI: 10.15408/ref.v13i4.912